Review of risk factors, treatment, and prevention of saphenous vein graft disease after coronary artery bypass grafting. Issue 12 (December 2018) - Gao, Jing; Liu, Yin; Li, Yu-Ming
Saphenous vein graft disease (SVGD) is a type of vascular disease that may develop after coronary artery bypass grafting (CABG). SVGD seriously affects the short-term and long-term effects of CABG and increases the incidence of major adverse cardiovascular events. It is very important to identify patients at greatest risk and carry out prevention and treatment measures to determine the risk factors for SVGD. Many factors contribute to SVGD when the vein is grafted into an arterial environment, such as surgery-related factors, smoking, diabetes mellitus, hyperlipidemia, and others. In this review, we discuss the risk factors for SVGD, current surgical and pharmacologic therapies with which to manage SVGD, and the prevention of SVGD.